ANALISIS PENGARUH IDENTITAS, CITRA DAN KEPERCAYAAN TERHADAP LOYALITAS MEREK - Seno Aji Wahyono; Catharina Aprilia Hellyani; Liem Gai Sin (Unitri Press, 2021)
This study aims to analyze the influence of identity, image, and trust on brand loyalty Honda motorcycles in Malang. Using quantitative methods with a population of 2,364 users in Malang City, a sample of 100 respondents was taken through purposive sampling. The data was obtained through a questionnaire survey which was tested with multiple linear regression. The results show that brand identity affects brand loyalty with a significance of 0.000 and a regression value of 0.376; in addition, the brand image has a significant value of 0.001 and a regression value of 0.341; brand trust has a significance value of 0.005 and a regression value of 0.295; and brand identity, brand image, and brand trust simultaneously affect brand loyalty with a significance value of 0.000 which indicates a positive relationship to brand loyalty. This is due to the advantages of Honda motorcycles in terms of advanced technological features and saving gasoline, as well as attractive appearance and design